1997
DOI: 10.2307/3579498
|View full text |Cite
|
Sign up to set email alerts
|

Non-Neoplastic and Neoplastic Thyroid Disease in Beagles Irradiated during Prenatal and Postnatal Development

Abstract: To evaluate the lifetime hazards of exposure to ionizing radiation, 1,680 beagles received whole-body exposures to 60Co gamma rays or sham exposures during development. Eight groups of 120 dogs each received mean doses of 16-18 or 81-88 cGy at 8, 28 or 55 days of gestation, or at 2 days after birth. One group of 120 dogs received a mean of 83 cGy at 70 days of age and one group of 240 dogs received a mean of 81 cGy at 365 days of age. Sham irradiations were given to 360 controls. Sexes were equally represented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In irradiated fetal lymphocytes from 40-yr-old survivors of in utero A-bomb exposure, Ohtaki et al (33) observed no evidence of a higher prevalence of chromosome translocations, except perhaps at very low doses. There have been a few animal studies, the most noteworthy a study of beagles irradiated both in utero and postnatally (34), with increased risk for thyroid disease found only among those who received radiation postnatally.…”
Section: Discussionmentioning
confidence: 98%
“…In irradiated fetal lymphocytes from 40-yr-old survivors of in utero A-bomb exposure, Ohtaki et al (33) observed no evidence of a higher prevalence of chromosome translocations, except perhaps at very low doses. There have been a few animal studies, the most noteworthy a study of beagles irradiated both in utero and postnatally (34), with increased risk for thyroid disease found only among those who received radiation postnatally.…”
Section: Discussionmentioning
confidence: 98%
“…In dogs the only known risk factors for thyroid neoplasia are hypothyroidism due to thyroiditis (Benjamin et al, 1996) and ionizing radiation (Benjamin et al, 1997). Studies in humans have suggested an association between thyroid neoplasia and (1) iodine deficiency or excess, (2) chronic excesses in thyroid-stimulating hormone (also known as thyrotropin; TSH) secretion, (3) ionizing radiation, and (4) gene abnormalities and oncogene expression.…”
Section: Pathogenesis Of Thyroid Tumorsmentioning
confidence: 99%
“…Hypothyroidism is mainly caused by lymphocytic thyroiditis or idiopathic thyroid atrophy [ 6 ]. Lymphocytic thyroiditis is considered as an autoimmune disorder [ 9 , 10 ] and has a hereditary predisposition [ 2 , 7 , 11 ]. It also has been suggested that the disease may be influenced by a major gene [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocytic thyroiditis is considered as an autoimmune disorder [ 9 , 10 ] and has a hereditary predisposition [ 2 , 7 , 11 ]. It also has been suggested that the disease may be influenced by a major gene [ 11 ]. Lymphocytic thyroiditis is known to be associated with the major histocompatibility complex (MHC) or dog leukocyte antigen (DLA) system class II allele [ 5 , 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation